Cuba. La esperanza de vida en años terminados en cero y cinco. 1900-2015. / Cuba. Life expentancy in calendar years ending in zero and five. 1900-2015. - Juan Carlos Albizu-Campos Espiñeira (Universidad de La Habana, 2021)
The paper deals with the reconstruction of the historical series of life tables for calendar years ended in zero and five, for the period 1900-2015 and the completion of the knowledge regarding the level and dynamics of mortality in Cuba and its most refined indicators, life expectancy at birth and infant mortality, giving continuity to previous works, but updating the evidence in light of the methodologies used today in this field, standardizing the procedures to avoid biases due to method changes for different subperiods, opening the study of mortality to ages 100 and over, by sex and for the entire population as a whole. Given the magnitude of the results generated, the reader will find in the annexes the information regarding survivors at exact single ages, the corresponding life expectancy at birth, the separation factor of deaths of children under one year of age and the specific mortality rate of the age group of 100 and over, for each calendar year ending at zero and five in the reference period. The mortality tables can then be reconstructed using the described methods. / RESUMEN El trabajo trata de la reconstrucción de la serie histórica de tablas de mortalidad para años terminados en cero y cinco, para el período 1900-2015, y el completamiento del conocimiento concerniente al nivel y la dinámica de mortalidad en Cuba y de sus indicadores más refinados, esperanza de vida al nacer y mortalidad infantil. Da continuidad a trabajos anteriores, pero actualiza la evidencia a la luz de las metodologías que actualmente se utilizan en este campo, homogeneizando los procedimientos para evitar sesgos poscambios de métodos para diferentes subperíodos, y abriendo el estudio de la mortalidad hasta las edades de 100 y más años, por sexos y para toda la población en su conjunto. Debido a la magnitud de resultados generados, el lector encontrará en los anexos la información concerniente a los sobrevivientes a edades simples exactas, la esperanza de vida al nacer correspondiente, el factor de separación de las defunciones de menores de un año y la tasa específica de mortalidad del grupo de edades de 100 y más años, para cada año calendario terminado en cero y cinco en el período de referencia. Las tablas de mortalidad pueden entonces ser reconstruidas utilizando los métodos descritos.